2021
DOI: 10.1002/adfm.202111208
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Endogenous Hydrogen Peroxide at Bone Defects Promotes Bone Repair

Abstract: Reactive oxygen species (ROS) plays a critical role in tissue repair, including bone. Therefore, detecting and regulating ROS is essential for monitoring and facilitating bone repair. In this study, for the first time, the spatiotemporal profile of ROS, represented by hydrogen peroxide (H2O2), in the bone injury microenvironment using photoacoustic imaging technique is visualized. The ROS levels significantly increase upon bone injury, peak at a certain stage of bone healing, and then gradually decrease toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 63 publications
2
56
0
Order By: Relevance
“…[43] Therefore, it has a unique advantage in imaging deep tissues such as bone, as has been demonstrated in our previous study. [5] In vivo H 2 O 2 elimination by composite hydrogels was also investigated in our study (Figure 6). The results display the changes in ROS in the bone of osteoporotic mice for the first time.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…[43] Therefore, it has a unique advantage in imaging deep tissues such as bone, as has been demonstrated in our previous study. [5] In vivo H 2 O 2 elimination by composite hydrogels was also investigated in our study (Figure 6). The results display the changes in ROS in the bone of osteoporotic mice for the first time.…”
Section: Discussionmentioning
confidence: 76%
“…Bone morphogenetic protein-2 (BMP-2)-associated peptide was loaded into hMNPs to promote bone repair. [5] In this study, MMS was prepared for the treatment of osteoporotic bone defects. Compared with previous hMNPs, MMS has a core-shell structure with porous CaP microspheres in the inner layer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to robust antioxidant properties, ARB-modi ed microspheres scavenge excessive ROS via the Nrf2-HO-1 signalling pathway. Li et al also demonstrated that hollow manganese dioxide nanoparticles (hMNPs) promoted bone defect repair by decomposing H 2 O 2 and generating oxygen to eliminate intracellular ROS [40]. Hence, we hypothesized that the dual regulation of in ammation and redox induced by GM-Lipo@ARB could boost cartilage regeneration in the microenvironment.…”
Section: Discussionmentioning
confidence: 96%